3D hierarchical Ag nanostructures formed on poly(acrylic acid) brushes grafted graphene oxide as promising SERS substrates. (6th February 2018) - Xing, Guoke; Wang, Ke; Li, Ping; Wang, Wenqin; Chen, Tao
Abstract: In this study, in situ generation of Ag nanostructures with various morphology on poly(acrylic acid) (PAA) brushes grafted onto graphene oxide (GO), for use as substrates for surface-enhanced Raman scattering (SERS), is demonstrated. The overall synthetic strategy involves the loading of Ag precursor ions ((Ag + and [Ag(NH3 )2 ] + ) onto PAA brush-grafted GO, followed by their in situ reduction to Ag nanostructures of various morphology using a reducing agent (NaBH4 or ascorbic acid). Novel 3D hierarchical flowerlike Ag nanostructures were obtained by using AgNO3 as precursor and ascorbic acid as reducing agent. Using 4-aminothiophenol as probe molecules, the as-prepared hierarchical Ag nanostructures exhibited excellent SERS performance, providing enhancement factors of ∼10 7 .